2021
DOI: 10.1007/s00170-021-08087-y
|View full text |Cite
|
Sign up to set email alerts
|

Edge finishing of large turbine casings using defined multi-edge and abrasive tools in automated cells

Abstract: Automate finishing processes is a global challenge in several industrial sectors. Concretely, when dealing with aero-engine components, only simple finishing processes are automated nowadays. Most of the high-added value components manufactured are finished hand working, using deburring and polishing manual techniques. The driver of the proposed work is to achieve the necessary knowledge to introduce in a production line a complete finishing process for automated robotic deburring applications with low machina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…The removal of burrs will require the use of deburring processes after the end of the milling process. For this reason, introducing deburring methods involving the help of robots could prove an effective solution for reducing the duration of manufacturing products incorporating thin walls [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…The removal of burrs will require the use of deburring processes after the end of the milling process. For this reason, introducing deburring methods involving the help of robots could prove an effective solution for reducing the duration of manufacturing products incorporating thin walls [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to improve the automation level of ultrasonic strengthening and realize the high precision strengthening of the blade surface, it is necessary to apply an industrial robot with a strengthening device to complete the process automatically. The advantages of industrial robots in the field of automated processing are very prominent, for example, a robotic complete finishing process is introduced for automated robotic deburring applications with low machinability materials on aero-engine casings with complex geometries [10], thus enabling a reduction in process operating time and improving processing quality. In the process of ultrasonic strengthening of the blade surface, the contact force between the strengthening tool and the workpiece surface is very important for forming a residual stress layer [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…18 From the literature review, it is found that researchers have utilized viscoelastic nature of the tool material for different finishing processes. The flexible tools reported by Rodrı´guez et al 19 is mainly based upon brush technology where abrasive balls of different sizes and materials are attached on top of the nylon filament. These types of tools are commonly used in finishing of internal holes, deburring, and blending of the edges.…”
Section: Introductionmentioning
confidence: 99%